Restrukturyzacja wielobranżowych podmiotów komunalnych. Koncepcje i realizacja - Żuk, Krzysztof (The Restructuring Process of Municipal Enterprises : Conceptions and Their Realization, 2007)
The scope of activities and tasks of a commune are specified in the Act on Local Government of 1990 and the Act on Municipal Management of 1996. The reform caused many problems related to the organizational form of economic activities conducted by communes and the transformation of municipal enterprises. The Communes faced the necessity to select an appropriate legal form for conducting economic activities which were indispensable from the point of view of the implementation of their tasks. In case of the majority of communes the selection of a legal form for conducting economic activities was either accidental or based on temporary benefits which were related to the selection of a given form. The problem of restructuring municipal services was not solved either, including the establishment of competing units. Local governments in starting transformation in the public utility sector had no clear and consistent policy for the emerging markets and privatization of public services. Local governments could not distinguish the most important goal - models of efficient management of public services in the market economy.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2007; nr 1161, s. 260-271